Changes in circulating adiponectin, leptin, glucose and C‐peptide in patients with ketosis‐prone diabetes. Issue 5 (17th December 2014) - Gupta, P.; Liu, Y.; Lapointe, M.; Yotsapon, T.; Sarat, S.; Cianflone, K.
Abstract: Aims: To evaluate circulating adipokines in people with ketosis‐prone diabetes, a heterogeneous disorder characterized by unprovoked ketoacidosis in people with previously unrecognized diabetes. Methods: Patients presenting with ketoacidosis with no previous diabetes diagnosis were compared with patients with previously established Type 1 diabetes. Baseline assessments of autoimmune status (A+/A‐), and β‐cell function (B+/B‐), as well as leptin and adiponectin levels during a standardized mixed‐meal tolerance test of 120 min, were performed. In all, 20 patients with heterogeneous ketosis‐prone diabetes and 12 patients with Type 1 diabetes were evaluated at baseline, 12 and 24 months. Results: At baseline, during a mixed‐meal tolerance test, glucose and adiponectin concentrations were lower in patients with ketosis‐prone diabetes than in those with Type 1 diabetes ( P = 0.0023 and P < 0.0001, respectively), whereas C‐peptide concentrations were higher, with no significant difference in leptin concentrations. Within 12 months, 11 patients with ketosis‐prone diabetes (all A‐/B+) were discontinued from insulin treatment (ketosis‐prone diabetes ‐ insulin group), while nine patients (four A‐B‐, four A+B‐ and one A‐B+) were maintained on insulin (ketosis‐prone diabetes + insulin group). Fasting C‐peptide levels increased significantly over 24 months in the ketosis‐prone diabetes ‐ insulin group ( P = 0.01), while HbA1c levels decreased ( P < 0.0001). Overall, the ketosis‐prone diabetes ‐ insulin group had a higher BMI ( P = 0.018), yet a lower fasting glucose concentration ( P = 0.003) compared with the ketosis‐prone diabetes + insulin group. Over 24 months, the mixed‐meal tolerance test area‐under‐the‐curve of C‐peptide increased in the ketosis‐prone diabetes ‐ insulin group, with no change in ketosis‐prone diabetes + insulin ( P < 0.0001). At 24 months, in spite of the higher BMI in the ketosis‐prone diabetes ‐ insulin group, mixed‐meal tolerance test glucose and leptin concentrations were significantly lower ( P < 0.0001 and P = 0.017, respectively), while adiponectin levels were higher ( P = 0.023) compared with the ketosis‐prone diabetes + insulin group. Conclusions: In spite of the higher BMI in the ketosis‐prone diabetes ‐ insulin group, lower leptin and higher adiponectin levels may contribute to improved β‐cell function and insulin sensitivity, as evidenced by lower glucose and higher C‐peptide levels. This allows insulin therapy to be withdrawn. What's new?: Ketosis‐prone diabetes is a heterogeneous disorder. At the time of presentation, patients with this disorder have unprovoked ketoacidosis and have not been previously identified as having diabetes (either Type 1 or Type 2). People with ketosis‐prone diabetes do not necessarily have the typical phenotype of autoimmune Type 1 diabetes but can be classified based on the presence/absence of autoantibodies (A+/A‐) and maintenance of a minimal β‐cell function (B+/B‐). People with A‐B+ ketosis‐prone diabetes comprise the largest subgroup of those with this disorder (˜50%), the majority of whom (50–80%) are able to maintain long‐term β‐cell functional reserve and successfully withdraw from insulin therapy after resolution of ketoacidosis. In the present study evaluating adipokines, patients who could be withdrawn from insulin (all patients with A‐B+ disease) had lower leptin and higher adiponectin levels, suggesting that, despite the patients having a higher BMI, these adipokines may contribute to their improved insulin sensitivity.